Neuromarketing: Deep Motivations of the Consumer in Premium Range Cars in the City of Riobamba - E. Cuzquillo Cusquillo; E. Yansapanta Carrillo; J. Montufar Guevara; J. Sánchez Lunavictoria (ESPOCH Congresses, 2021)
Abstract In a society where information and knowledge have become essential cornerstones of economic development, it is important that companies allocate the necessary resources to evaluate studies based on consumer behavior and the psychological aspects that influence purchasing decisions. For this reason, this research aimed to understand the motivations of consumers, and the symbolic emotional relationship between the consumer and the brand and model of Premium Range cars in the city of Riobamba. With the advancement of marketing and its link with the study of neuroscience, efficient tools have been developed that allow us to better understand the reasons why people acquire a vehicle. This research had a quasi-experimental design and employed qualitative and quantitative approaches through using biometric equipment including eye tracking. It was determined that there were conscious and unconscious factors that influenced consumers when deciding between makes and models in acquiring a Premium Range vehicle. Personality was key in defining the brand preferred and the model chosen.